Prognostic significance of TMEM131L in glioma and establishment of oxidative stress prognostic model - Shan, Li; Zhu, Xiaoli; Qiu, Hui-Zhu; Zuo, Er-Dong; Cheng, Xu (Frontiers in Neurology, 2023)
Gliomas are the most aggressive of all brain tumors, TMEM131L was significantly expressed in glioma tissues in this study. The relevance of TMEM131L in the diagnosis and clinical prognosis of GBM and LGG was also verified by additional clinical correlation analysis and survival analysis. The AUC of ROC curve reflected the diagnostic effect of TMEM131L on clinicopathologic features of glioma. A unique molecular marker for the poor prognosis of OS, PFI, and DSS in GCB&LGG patients, TMEM131L might be employed, according to time-dependent ROC curves and Kaplan-Meier survival analysis at 1,3, and 5 years. The potential methylation sites of TMEM131L were selected by correlation analysis between TMEM131L and DNA methylation sites. At the same time, TMEM131L was significantly correlated with matrix, immunity and estimated scores of GBM and LGG. And CIBERSORT analysis showed significant correlation with immune checkpoint and infiltration of 22 kinds of immune cells. Co-expression genes of TMEM131L associated with oxidative stress phenotype were screened by LASSO logistic regression analysis. Nomogram and calibration curves further confirm that the prognostic model composed of SYT1, CREB3L3, ITPR1, RASGRF2, PDX1 and RASGRF1 has good stability and potential application value for poor prognosis in glioma patients.